The Influence of Standard Operating Procedures and Supervision on Employee Work Productivity Through Work Discipline - Husna, Sari Fatul; Hendriani, Susi; Novrianti, Dian Puspita (CV. Rayyan Dwi Bharata, 2023)
This research was conducted at Perum Jamkrindo Pekanbaru Branch. The purpose of this study is to find out whether Standard Operating Procedures (SOP) and supervision affect employee work productivity and whether work discipline is able to mediate the effect of SOP and supervision on employee work productivity at Perum Jamkrindo Pekanbaru Branch. The population in this study were all employees of Perum Jamkrindo Pekanbaru Branch, totaling 42 employees. The sampling method used is total sampling, namely as many as 42 respondents. The results of this study are, (1) There is a positive and significant influence between SOP and employee work productivity, (2) There is a positive and significant influence between supervision and employee work productivity, (3) There is a positive and significant influence between SOP and work discipline, (4) There is a positive and significant influence between supervision and work discipline, (5) Work discipline has a positive and significant effect on employee work productivity, (6) There is a positive and significant influence on SOP on employee work productivity through work discipline and, (7) There is a positive and significant influence on supervision on employee productivity through work discipline.